Fampridine‐PR (prolonged released 4‐aminopyridine) is not effective in patients with inflammatory demyelination of the peripheral nervous system. Issue 2 (1st June 2016) - Leussink, Verena‐Isabell; Stettner, Mark; Warnke, Clemens; Hartung, Hans‐Peter
Abstract: Fampridine‐PR is a voltage‐gated potassium channel inhibitor potentially improving nerve conduction in demyelinated axons. Based on its established clinical efficacy in patients with demyelination in the central nervous system, we assessed if fampridine‐PR is also effective in patients with inflammatory demyelination of the peripheral nerve. In this small open‐label study, 10 patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) were treated with fampridine‐PR 10 mg BID for 28 days and assessed clinically as well as by nerve conduction studies. In this study, Fampridine‐PR failed to improve CIDP based on clinical measures and nerve conduction studies. Our findings suggest that Fampridine‐PR appears to be ineffective in demyelinating polyneuropathies. These observations may indicate a more complex mode of action beyond improving action potential conduction in demyelinated axons.